Visible light photocatalytic composite material and preparation method thereof
By combining magnetic Fe3O4 with photocatalytic shell (TiO2/g-C3N4) and performing surface functionalization, the efficiency and stability problems of existing photocatalytic materials when dealing with complex pollutant systems are solved, and efficient and circulating multiple pollutants are achieved.
Patent Information
- Application Number
- CN202510113246.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-24
AI Technical Summary
When existing photocatalytic materials deal with complex pollutants, the treatment efficiency of multiple pollutants and the long-term stability of catalysts are weak. At the same time, the separation and recycling of powdered photocatalysts limit their large-scale promotion and application.
The magnetic Fe3O4 is organically combined with the photocatalytic shell (TiO2/g-C3N4), and the photogenerated electron-hole separation efficiency is significantly improved by using heterojunction, and the surface functionalization is used to achieve efficient adsorption and reduction of organic components and heavy metal ions in wastewater.
The photocatalytic materials with wide spectrum response, high selective removal ability, strong stability and recyclable use are achieved, solving the problems of narrow visible light response range of traditional photocatalytic materials, difficulty in recycling catalysts, and poor selective removal of heavy metals.
Smart Images

Figure CN119549182A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic materials, and in particular relates to a visible light photocatalytic composite material and a preparation method thereof. Background Art
[0002] With the acceleration of the process of social industrialization, heavy metal pollution in water has become a core issue of concern in the environmental field. Cr, which is highly toxic, difficult to degrade and bioaccumulate, 3+ , Pb 2+ Heavy metal ions such as ions seriously threaten ecosystems and human health. At present, traditional sewage treatment methods such as chemical precipitation, adsorption and ion exchange have limitations in operating costs, selectivity and treatment efficiency, and are increasingly unable to meet the needs of complex pollution systems. Photocatalytic technology has become an ideal choice for treating sewage containing heavy metals due to its low energy consumption, green environmental protection and high efficiency in degrading a variety of pollutants. Although many studies have significantly improved the visible light utilization efficiency and heavy metal removal ability of photocatalysts through methods such as band gap regulation, surface functional modification and heterogeneous structure construction, they are still relatively weak in terms of treatment efficiency for multiple pollutants in complex pollution systems and long-term stability of catalysts. In addition, the separation and recovery of powdered photocatalysts after sewage treatment also limits their large-scale promotion and application.
[0003] Therefore, the development of new photocatalytic materials with wide spectral response, highly selective removal ability, strong stability and recyclability is a key direction to promote the practical engineering application of photocatalytic technology. Summary of the invention
[0004] In view of the above situation, the present invention provides a visible light photocatalytic composite material and a preparation method thereof, which organically combines magnetic Fe3O4 with a photocatalytic shell (TiO2 / g-C3N4), and utilizes a heterojunction to significantly improve the photogenerated electron-hole separation efficiency based on high-efficiency photocatalytic performance and magnetic separation function; through surface functionalization, efficient adsorption and reduction of organic components and specific heavy metal ions in sewage are achieved, the raw materials used have strong chemical stability, and the prepared photocatalytic composite material can be recycled multiple times, thereby solving the problems of narrow visible light response range, difficult catalyst recovery and poor heavy metal selective removal effect in the prior art.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: The invention provides a visible light photocatalytic composite material, which comprises the following raw materials by weight: 10-50 g of magnetic nanocore, 20-80 g of TiO2 precursor, 20-80 g of stabilizer, 40-100 g of g-C3N4 precursor and 50-200 g of modifier.
[0006] Furthermore, the magnetic nanocore comprises the following raw materials by weight: 27-54 g of FeCl3·6H2O, 20-40 g of FeSO4·7H2O and 50-100 g of 25% (v / v, volume fraction) NH4OH solution.
[0007] Furthermore, the TiO2 precursor is selected from any one of Ti(OBu)4 (tetrabutyl titanate), Ti(OiPr)4 (tetraisopropyl titanate) and LiTiO3 (lithium titanate).
[0008] Furthermore, the stabilizer is selected from any one of acetic acid, acetylacetone, ethyl acetate and triethanolamine.
[0009] Furthermore, the g-C3N4 precursor is selected from any one of urea, dicyandiamide, thiourea and citrulline.
[0010] The preparation method of the magnetic nanocore comprises the following steps: S1: Weigh 27-54 g FeCl3·6H2O, dissolve FeCl3·6H2O in deionized water according to a mass volume ratio of 2.7-5.4 g:100 mL to obtain a FeCl3 solution; S2: Weigh 20-40 g of FeSO4·7H2O, add it to the FeCl3 solution obtained in step S1, and stir until it is completely dissolved to obtain an iron salt solution; S3: Under a nitrogen atmosphere, the iron salt solution obtained in step S2 is heated to 70°C while stirring, 50-100g of 25% NH4OH solution is weighed and added as a precipitant, the pH is adjusted and maintained in the range of 10.0±0.2, and stirring is continued for 1 h at a stirring speed of 80 rpm to generate a black Fe3O4 precipitate; S4: Separate the Fe3O4 precipitate generated in step S3 from the solution using a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times respectively, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain a magnetic nanocore.
[0011] The present invention also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps: Step 1: Weigh 10-50 g of magnetic nanocores, disperse them in 40% (v / v) ethanol aqueous solution at a mass volume ratio of 1-5 g: 60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion; Step 2: Weigh 20-80 g of TiO2 precursor and 20-80 g of stabilizer, mix and stir evenly, and slowly add to the dispersion obtained in step 1 to obtain Fe3O4@TiO2 reaction solution; Step 3: Weigh 40-100 g of g-C3N4 precursor and add it to the Fe3O4@TiO2 reaction solution obtained in step 2, stir evenly to obtain a primary mixed solution, transfer the primary mixed solution to a high-pressure reactor, react at 40 MPa and 180°C for 6 h, and after the reaction is completed, cool to room temperature to produce a precipitate, collect the precipitate with a magnetic separator and wash it with deionized water and anhydrous ethanol three times in sequence, dry it in an oven at 60°C for 12 h to obtain dry particles, calcine the dry particles in a tubular furnace at a heating rate of 5°C / min, and keep it at 550°C for 2 h to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Soak the Fe3O4@TiO2 / g-C3N4 obtained in step 3 in a H2SO4-H2O2 mixed solution (volume ratio of 1:1) for 20 min at a mass volume ratio of 1 g:5 mL. A precipitate is formed. The precipitate is filtered, washed with deionized water, and dried to obtain hydroxylated Fe3O4@TiO2 / g-C3N4. Step 5: Disperse the hydroxylated Fe3O4@TiO2 / g-C3N4 obtained in step 4 in a dispersant, weigh 50-200 g of a modifier and add it to react, transfer the precipitate and wash and dry it with deionized water or anhydrous ethanol to obtain a modified Fe3O4@TiO2 / g-C3N4, i.e., a visible light photocatalytic composite material.
[0012] Furthermore, the modifier is selected from any one of MPTS (3-mercaptopropyltriethoxysilane), ethylenediamine, chlorosulfonic acid and EDTA-2Na (disodium ethylenediaminetetraacetate).
[0013] Furthermore, the dispersant is selected from any one of deionized water, anhydrous ethanol, dichloromethane and an ethanol-citric acid mixed solution (volume ratio 1:1).
[0014] The beneficial effects achieved by the present invention are as follows: The visible light photocatalytic composite material prepared by the present invention is a photocatalytic material with a heterojunction constructed by compounding visible light responsive g-C3N4 with TiO2. The g-C3N4 provides a narrow bandgap structure to enhance the utilization rate of visible light, and can absorb visible light to generate photogenerated electrons and holes under light. The photogenerated electrons are transferred to the TiO2 interface through the heterojunction, and form superoxide free radicals with oxygen molecules in the environment or form hydroxyl free radicals with water molecules / hydroxyl groups, which attack and degrade organic pollutants into non-toxic small molecules, thereby achieving environmental governance. Meanwhile, the high surface activity of TiO2 further improves the photocatalytic reaction rate, avoids the rapid recombination of electrons and holes, and further improves the efficiency of redox reactions. The two significantly improve the ability of photocatalytic degradation of organic pollutants through interface synergy. Meanwhile, after the action of a modifier, groups such as thiol, amino, carboxyl and sulfonic acid groups can be introduced on the surface of the material, which can specifically adsorb or chelate Hg 2+ 、Cd 2+ , Pb 2+ Cr 3+ and Zn 2+ It can simultaneously remove heavy metal ions in water and demonstrate excellent dual-functional treatment performance; the adsorbed heavy metal ions can be further converted into low-toxic or stable states by reacting with oxidative intermediates generated in the photocatalytic process, thereby achieving deep removal; in addition, the adsorption process reduces the concentration of heavy metal ions in the solution, weakens its inhibitory effect on the photocatalytic process, improves the photocatalytic efficiency, and realizes the integrated treatment of multiple pollutants.
[0015] Compared with the prior art, the material of the present invention has both recyclability and multifunctionality, and solves the problem that traditional photocatalytic materials are difficult to deal with organic matter and heavy metal pollution at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The photocatalytic performance test results of the modified Fe3O4@TiO2 / g-C3N4 prepared in Example 1 and Examples 5-7; Figure 2 Fourier transform infrared spectroscopy analysis results of the modified Fe3O4@TiO2 / g-C3N4 prepared in Examples 1-4; Figure 3 X-ray diffraction test results of the modified Fe3O4@TiO2 / g-C3N4 prepared in Examples 1-4; Figure 4 UV-visible diffuse reflectance spectrum test results of modified Fe3O4@TiO2 / g-C3N4 prepared in Example 1 and Examples 5-7; Figure 5The test results of the heavy metal ion adsorption capacity of the modified Fe3O4@TiO2 / g-C3N4 prepared in Examples 1-4; Figure 6 These are the results of investigating the photocatalytic performance of the thiolated Fe3O4@TiO2 / g-C3N4 prepared in Example 1 after recycling.
[0017] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.
[0020] In the following examples, unless otherwise specified, conventional methods are used; the materials used in the following examples, unless otherwise specified, are all new materials purchased from the market.
[0021] Example 1: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocores, 450 g of Ti(OBu), 50 g of acetic acid, 80 g of urea and 120 g of MPTS.
[0022] The magnetic nanocore includes the following raw materials by weight: 40 g of FeCl3·6H2O, 30 g of FeSO4·7H2O and 80 g of 25% NH4OH solution. The specific preparation method is as follows: S1: Weigh 40 g of FeCl3·6H2O and dissolve it in deionized water at a mass volume ratio of 4 g:100 mL to obtain a FeCl3 solution; S2: Weigh 30 g of FeSO4·7H2O, add it to the FeCl3 solution obtained in step S1, and stir until it is completely dissolved to obtain an iron salt solution; S3: Under a nitrogen atmosphere, the iron salt solution obtained in step S2 was heated to 70°C while stirring, 80 g of 25% NH4OH solution was weighed and added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate a black Fe3O4 precipitate; S4: Separate the Fe3O4 precipitate generated in step S3 from the solution using a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times respectively, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain a magnetic nanocore.
[0023] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps: Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion; Step 2: Weigh 50 g Ti(OBu)4 and 50 g acetic acid, mix and stir evenly, and slowly add them to the dispersion obtained in step 1 to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh 80 g of urea and add it to the Fe3O4@TiO2 reaction solution obtained in step 2, stir evenly to obtain a primary mixed solution, transfer the primary mixed solution to a high-pressure reactor, react at 40 MPa and 180°C for 6 h, and after the reaction is completed, cool to room temperature to produce a precipitate, collect the precipitate with a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times in sequence, dry it in an oven at 60°C for 12 h to obtain dry particles, calcine the dry particles in a tubular furnace at a heating rate of 5°C / min, and keep it at 550°C for 2 h to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Soak the Fe3O4@TiO2 / g-C3N4 obtained in step 3 in a H2SO4-H2O2 mixed solution at a mass volume ratio of 1 g:5 mL for 20 min, and a precipitate will appear. Filter the precipitate, wash it with deionized water, and dry it to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Disperse the hydroxylated Fe3O4@TiO2 / g-C3N4 in anhydrous ethanol at a mass volume ratio of 1 g:10 mL, measure 0.5 mL of acetic acid as a catalyst and weigh 120 g of MPTS and add them, react at room temperature for 4 h, transfer the precipitate and wash and dry it with anhydrous ethanol to obtain thiolated Fe3O4@TiO2 / g-C3N4, that is, the visible light photocatalytic composite material.
[0024] Example 2: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 50 g of magnetic nanocores, 420 g of Ti(OBu), 20 g of acetic acid, 40 g of urea and 50 g of ethylenediamine.
[0025] The magnetic nanocore includes the following raw materials by weight: 27 g of FeCl3·6H2O, 20 g of FeSO4·7H2O and 50 g of 25% NH4OH solution. The specific preparation method is as follows: S1: Weigh 27 g FeCl3·6H2O and dissolve it in deionized water at a mass volume ratio of 2.7 g:100 mL to obtain a FeCl3 solution; S2: Weigh 20 g of FeSO4·7H2O, add it to the FeCl3 solution obtained in step S1, and stir until it is completely dissolved to obtain an iron salt solution; S3: Under a nitrogen atmosphere, the iron salt solution obtained in step S2 was heated to 70°C while stirring, 50 g of 25% NH4OH solution was weighed and added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate a black Fe3O4 precipitate; S4: Separate the Fe3O4 precipitate generated in step S3 from the solution using a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times respectively, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain a magnetic nanocore.
[0026] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps: Step 1: Weigh 50 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 5 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion; Step 2: Weigh 20 g Ti(OBu)4 and 20 g acetic acid, mix and stir evenly, and slowly add them to the dispersion obtained in step 1 to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh 40 g of urea and add it to the Fe3O4@TiO2 reaction solution obtained in step 2, stir evenly to obtain a primary mixed solution, transfer the primary mixed solution to a high-pressure reactor, react at 40 MPa and 180°C for 6 h, and after the reaction is completed, cool to room temperature to produce a precipitate, collect the precipitate with a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times in sequence, dry it in an oven at 60°C for 12 h to obtain dry particles, calcine the dry particles in a tubular furnace at a heating rate of 5°C / min, and keep it at 550°C for 2 h to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Soak the Fe3O4@TiO2 / g-C3N4 obtained in step 3 in a H2SO4-H2O2 mixed solution at a mass volume ratio of 1 g:5 mL for 20 min, and a precipitate will appear. Filter the precipitate, wash it with deionized water, and dry it to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Soak the hydroxylated Fe3O4@TiO2 / g-C3N4 in an ethanol-citric acid mixed solution (volume ratio of 1:1) at a mass volume ratio of 1 g:10 mL for reaction for 2 h. Transfer the precipitate, wash it with deionized water, and dry it to obtain carboxylated Fe3O4@TiO2 / g-C3N4. Weigh 50 g of ethylenediamine and dissolve it in deionized water to prepare an ethylenediamine solution with a concentration of 6 mg / mL. Transfer the carboxylated Fe3O4@TiO2 / g-C3N4 to the activator at a mass volume ratio of 1 g:10 mL. The activator is prepared from EDC (1-ethyl-(3-dimethylaminopropyl) carbodiimide), NHS (N-hydroxysuccinimide) and MES buffer solution at pH 6.0, where the concentrations of EDC and NHS are 3.8 mg / mL and 2.8 mg / mL, respectively. After stirring and activating for 30 min, add an ethylenediamine solution of equal volume to the activator and continue stirring at 30 °C for 40 min. min for the amidation reaction. After the reaction is completed, the precipitate is transferred, washed with deionized water and dried to obtain the amination Fe3O4@TiO2 / g-C3N4, i.e., the visible light photocatalytic composite material.
[0027] Example 3: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 10 g of magnetic nanocores, 480 g of Ti(OBu), 80 g of acetic acid, 100 g of urea and 200 g of chlorosulfonic acid.
[0028] The magnetic nanocore includes the following raw materials by weight: 54 g of FeCl3·6H2O, 40 g of FeSO4·7H2O and 100 g of 25% NH4OH solution. The specific preparation method is as follows: S1: Weigh 54 g FeCl3·6H2O and dissolve it in deionized water at a mass volume ratio of 5.4 g:100 mL to obtain a FeCl3 solution; S2: Weigh 40 g of FeSO4·7H2O, add it to the FeCl3 solution obtained in step S1, and stir until it is completely dissolved to obtain an iron salt solution; S3: Under a nitrogen atmosphere, the iron salt solution obtained in step S2 was heated to 70°C while stirring, 100 g of 25% NH4OH solution was weighed and added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate a black Fe3O4 precipitate; S4: Separate the Fe3O4 precipitate generated in step S3 from the solution using a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times respectively, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain a magnetic nanocore.
[0029] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps: Step 1: Weigh 10 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 1 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion; Step 2: Weigh 80 g Ti(OBu)4 and 80 g acetic acid, mix and stir evenly, and slowly add them to the dispersion obtained in step 1 to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh 100 g of urea and add it to the Fe3O4@TiO2 reaction solution obtained in step 2, stir evenly to obtain a primary mixed solution, transfer the primary mixed solution to a high-pressure reactor, react at 40 MPa and 180°C for 6 h, and after the reaction is completed, cool to room temperature to produce a precipitate, collect the precipitate with a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times in sequence, dry it in an oven at 60°C for 12 h to obtain dry particles, calcine the dry particles in a tubular furnace at a heating rate of 5°C / min, and keep it at 550°C for 2 h to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Soak the Fe3O4@TiO2 / g-C3N4 obtained in step 3 in a H2SO4-H2O2 mixed solution at a mass volume ratio of 1 g:5 mL for 20 min, and a precipitate will appear. Filter the precipitate, wash it with deionized water, and dry it to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Disperse the hydroxylated Fe3O4@TiO2 / g-C3N4 in dichloromethane at a mass volume ratio of 1 g:50 mL, and perform ultrasonic dispersion at 100 W for 10 min to obtain a suspension. Slowly add 200 g of chlorosulfonic acid into the suspension while stirring under ice bath conditions. After the addition is completed, continue stirring and react for 2 h. After completion, transfer the reaction solution to ice water to neutralize the generated HCl. Transfer the precipitate, wash it with deionized water, and dry it to obtain the sulfonated Fe3O4@TiO2 / g-C3N4, i.e., the visible light photocatalytic composite material.
[0030] Example 4: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocores, 450 g of Ti(OBu), 50 g of acetic acid, 80 g of urea and 140 g of EDTA-2Na.
[0031] The magnetic nanocore includes the following raw materials by weight: 40 g of FeCl3·6H2O, 30 g of FeSO4·7H2O and 80 g of 25% NH4OH solution. The specific preparation method is as follows: S1: Weigh 40 g of FeCl3·6H2O and dissolve it in deionized water at a mass volume ratio of 4 g:100 mL to obtain a FeCl3 solution; S2: Weigh 30 g of FeSO4·7H2O, add it to the FeCl3 solution obtained in step S1, and stir until it is completely dissolved to obtain an iron salt solution; S3: Under a nitrogen atmosphere, the iron salt solution obtained in step S2 was heated to 70°C while stirring, 80 g of 25% NH4OH solution was weighed and added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate a black Fe3O4 precipitate; S4: Separate the Fe3O4 precipitate generated in step S3 from the solution using a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times respectively, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain a magnetic nanocore.
[0032] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps: Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion; Step 2: Weigh 50 g Ti(OBu)4 and 50 g acetic acid, mix and stir evenly, and slowly add them to the dispersion obtained in step 1 to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh 80 g of urea and add it to the Fe3O4@TiO2 reaction solution obtained in step 2, stir evenly to obtain a primary mixed solution, transfer the primary mixed solution to a high-pressure reactor, react at 40 MPa and 180°C for 6 h, and after the reaction is completed, cool to room temperature to produce a precipitate, collect the precipitate with a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times in sequence, dry it in an oven at 60°C for 12 h to obtain dry particles, calcine the dry particles in a tubular furnace at a heating rate of 5°C / min, and keep it at 550°C for 2 h to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Soak the Fe3O4@TiO2 / g-C3N4 obtained in step 3 in a H2SO4-H2O2 mixed solution at a mass volume ratio of 1 g:5 mL for 20 min, and a precipitate will appear. Filter the precipitate, wash it with deionized water, and dry it to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Weigh 140 g of EDTA-2Na and dissolve it in deionized water to prepare a 20 mg / mL EDTA-2Na solution. Disperse the hydroxylated Fe3O4@TiO2 / g-C3N4 in deionized water according to a mass volume ratio of 1 g:20 mL. Add an equal volume of EDTA-2Na solution, heat to 50 °C, stir and react for 4 h, transfer the precipitate, wash it with anhydrous ethanol, and dry it to obtain EDTA-treated Fe3O4@TiO2 / g-C3N4, which is a visible light photocatalytic composite material.
[0033] Example 5: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocores, 450 g of Ti(OiPr), 50 g of acetylacetone, 80 g of thiourea and 120 g of MPTS.
[0034] The magnetic nanocore includes the following raw materials by weight: 40 g of FeCl3·6H2O, 30 g of FeSO4·7H2O and 80 g of 25% NH4OH solution. The specific preparation method is as follows: S1: Weigh 40 g FeCl3·6H2O and dissolve it in deionized water at a mass volume ratio of 4 g:100 mL to obtain a FeCl3 solution; S2: Weigh 30 g of FeSO4·7H2O, add it to the FeCl3 solution obtained in step S1, and stir until it is completely dissolved to obtain an iron salt solution; S3: Under a nitrogen atmosphere, the iron salt solution obtained in step S2 was heated to 70°C while stirring, 80 g of 25% NH4OH solution was weighed and added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate a black Fe3O4 precipitate; S4: Separate the Fe3O4 precipitate generated in step S3 from the solution using a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times respectively, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain a magnetic nanocore.
[0035] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps: Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion; Step 2: Weigh 50 g Ti(OiPr)4 and 50 g acetylacetone, mix and stir evenly, and slowly add them to the dispersion obtained in step 1 to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh 80 g of thiourea and add it to the Fe3O4@TiO2 reaction solution obtained in step 2, stir evenly to obtain a primary mixed solution, transfer the primary mixed solution to a high-pressure reactor, react at 40 MPa and 180°C for 6 h, and after the reaction is completed, cool to room temperature to produce a precipitate, collect the precipitate with a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times in sequence, dry it in an oven at 60°C for 12 h to obtain dry particles, calcine the dry particles in a tubular furnace at a heating rate of 5°C / min, and keep it at 550°C for 2 h to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Soak the Fe3O4@TiO2 / g-C3N4 obtained in step 3 in a H2SO4-H2O2 mixed solution at a mass volume ratio of 1 g:5 mL for 20 min, and a precipitate will appear. Filter the precipitate, wash it with deionized water, and dry it to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Disperse the hydroxylated Fe3O4@TiO2 / g-C3N4 in anhydrous ethanol at a mass volume ratio of 1 g:10 mL, weigh 120 g of MPTS and 0.5 mL of acetic acid as catalyst, react at room temperature for 4 h, transfer the precipitate and wash and dry it with anhydrous ethanol to obtain thiolated Fe3O4@TiO2 / g-C3N4, i.e., the visible light photocatalytic composite material.
[0036] Example 6: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocores, 50 g of LiTiO3, 50 g of ethyl acetate, 80 g of dicyandiamide and 120 g of MPTS.
[0037] The magnetic nanocore includes the following raw materials by weight: 40 g of FeCl3·6H2O, 30 g of FeSO4·7H2O and 80 g of 25% NH4OH solution. The specific preparation method is as follows: S1: Weigh 40 g FeCl3·6H2O and dissolve it in deionized water at a mass volume ratio of 4 g:100 mL to obtain a FeCl3 solution; S2: Weigh 30 g of FeSO4·7H2O, add it to the FeCl3 solution obtained in step S1, and stir until it is completely dissolved to obtain an iron salt solution; S3: Under a nitrogen atmosphere, the iron salt solution obtained in step S2 was heated to 70°C while stirring, 80 g of 25% NH4OH solution was weighed and added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate a black Fe3O4 precipitate; S4: Separate the Fe3O4 precipitate generated in step S3 from the solution using a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times respectively, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain a magnetic nanocore.
[0038] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps: Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion; Step 2: Weigh 50 g LiTiO3 and 50 g ethyl acetate, mix and stir evenly, and slowly add them to the dispersion obtained in step 1 to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh 80 g of dicyandiamide and add it to the Fe3O4@TiO2 reaction solution obtained in step 2, stir evenly to obtain a primary mixed solution, transfer the primary mixed solution to a high-pressure reactor, react at 40 MPa and 180°C for 6 h, and after the reaction is completed, cool to room temperature to produce a precipitate, collect the precipitate with a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times in sequence, dry it in an oven at 60°C for 12 h to obtain dry particles, calcine the dry particles in a tubular furnace at a heating rate of 5°C / min, and keep it at 550°C for 2 h to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Soak the Fe3O4@TiO2 / g-C3N4 obtained in step 3 in a H2SO4-H2O2 mixed solution at a mass volume ratio of 1 g:5 mL for 20 min, and a precipitate will appear. Filter the precipitate, wash it with deionized water, and dry it to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Disperse the hydroxylated Fe3O4@TiO2 / g-C3N4 in anhydrous ethanol at a mass volume ratio of 1 g:10 mL, weigh 120 g of MPTS and 0.5 mL of acetic acid as catalyst, react at room temperature for 4 h, transfer the precipitate and wash and dry it with anhydrous ethanol to obtain thiolated Fe3O4@TiO2 / g-C3N4, i.e., the visible light photocatalytic composite material.
[0039] Example 7: This example provides a visible light photocatalytic composite material, which includes the following raw materials by weight: 30 g of magnetic nanocores, 450 g of Ti(OBu), 50 g of triethanolamine, 80 g of citrulline and 120 g of MPTS.
[0040] The magnetic nanocore includes the following raw materials by weight: 40 g of FeCl3·6H2O, 30 g of FeSO4·7H2O and 80 g of 25% NH4OH solution. The specific preparation method is as follows: S1: Weigh 40 g of FeCl3·6H2O and dissolve it in deionized water at a mass volume ratio of 4 g:100 mL to obtain a FeCl3 solution; S2: Weigh 30 g of FeSO4·7H2O, add it to the FeCl3 solution obtained in step S1, and stir until it is completely dissolved to obtain an iron salt solution; S3: Under a nitrogen atmosphere, the iron salt solution obtained in step S2 was heated to 70°C while stirring, 80 g of 25% NH4OH solution was weighed and added as a precipitant, the pH was adjusted and maintained at 10.0, and stirring was continued for 1 h at a stirring speed of 80 rpm to generate a black Fe3O4 precipitate; S4: Separate the Fe3O4 precipitate generated in step S3 from the solution using a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times respectively, and then dry it in a vacuum drying oven at 60°C for 12 h to obtain a magnetic nanocore.
[0041] This embodiment also provides a method for preparing a visible light photocatalytic composite material, which specifically comprises the following steps: Step 1: Weigh 30 g of magnetic nanocores, disperse them in 40% ethanol aqueous solution at a mass volume ratio of 3 g:60 mL, and perform ultrasonic treatment at 120 W for 30 min to obtain a dispersion; Step 2: Weigh 50 g Ti(OBu)4 and 50 g triethanolamine, mix and stir evenly, and slowly add them to the dispersion obtained in step 1 to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh 80 g of citrulline and add it to the Fe3O4@TiO2 reaction solution obtained in step 2, stir evenly to obtain a primary mixed solution, transfer the primary mixed solution to a high-pressure reactor, react at 40 MPa and 180°C for 6 h, and after the reaction is completed, cool to room temperature to produce a precipitate, collect the precipitate with a magnetic separator, wash the precipitate with deionized water and anhydrous ethanol three times in sequence, dry it in an oven at 60°C for 12 h to obtain dry particles, calcine the dry particles in a tubular furnace at a heating rate of 5°C / min, and keep it at 550°C for 2 h to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Soak the Fe3O4@TiO2 / g-C3N4 obtained in step 3 in a H2SO4-H2O2 mixed solution at a mass volume ratio of 1 g:5 mL for 20 min, and a precipitate will appear. Filter the precipitate, wash it with deionized water, and dry it to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Disperse the hydroxylated Fe3O4@TiO2 / g-C3N4 in anhydrous ethanol at a mass volume ratio of 1 g:10 mL, weigh 120 g of MPTS and 0.5 mL of acetic acid as catalyst, react at room temperature for 4 h, transfer the precipitate and wash and dry it with anhydrous ethanol to obtain thiolated Fe3O4@TiO2 / g-C3N4, i.e., the visible light photocatalytic composite material.
[0042] Photocatalytic performance test Weigh 50 mg of each of the modified Fe3O4@TiO2 / g-C3N4 prepared in Example 1 and Example 5-7 into a beaker, add 100 mL of methyl orange solution (10 mg / mL), transfer to a photochemical reactor after 120 W ultrasound for 5 min in a dark place, stir for 30 min in a dark place, turn on the light source, take 4 mL of the solution at 5, 10, 20, 30, 40, 50 and 60 min, and after sieving through a molecular sieve, detect the absorbance (A) of the solution at a wavelength of 463 nm, and calculate the photocatalytic degradation rate according to the following formula: C%=(A0-A t ) / A0×100%, A0 is the absorbance of the solution before turning on the light source, A t is the absorbance value of the solution detected at different time points, the results are shown in Figure 1 .
[0043] FT-IR (Fourier Transform Infrared Spectroscopy) Analysis The Fe3O4@TiO2 / g-C3N4 prepared in Example 1-4 and modified by the modifier was subjected to FT-IR analysis using the KBr tablet method. The results are shown in Figure 2 .
[0044] XRD (X-ray diffraction) analysis The composition and crystal structure of the Fe3O4@TiO2 / g-C3N4 samples modified by the modifier prepared in Examples 1-4 were analyzed by X-ray diffractometer. α The working current and voltage were 40 mA and 40 kV respectively. The results are shown in Figure 3 .
[0045] Light absorption characteristics investigation The Fe3O4@TiO2 / g-C3N4 modified by the modifier prepared in Example 1 and Examples 5-7 were subjected to UV-Vis DRS (ultraviolet-visible diffuse reflectance spectroscopy) characterization analysis. The results are shown in Figure 4 .
[0046] Investigation on the adsorption performance of heavy metal ions Take 200 mg / L concentration of Pb 2+ 、Cd 2+ 、Ag + , Cu 2+ Cr 3+ 、Al 3+ 100 mL of heavy metal ion solution, 50 mg of Fe3O4@TiO2 / g-C3N4 modified by the modifier prepared in Examples 1-4 were added to the above solutions respectively, and the mixture was shaken on a shaker at 25°C and 150 rpm for 24 h. The reaction solution was filtered with a 0.45 μm filter membrane, and the mass concentration of heavy metal ions after filtration was determined by an atomic absorption spectrometer. The heavy metal ion adsorption capacity was determined. The results are shown in Figure 5 .
[0047] Reuse performance tests Weigh 50 mg of the thiolated Fe3O4@TiO2 / g-C3N4 prepared in Example 1, add 100 mL of methyl orange solution (10 mg / mL), transfer to a photochemical reactor after 120 W ultrasound for 5 min in a dark place, stir for 30 min in a dark place, turn on the light source, and take the supernatant after 60 min to detect the absorbance of the solution; take out the thiolated Fe3O4@TiO2 / g-C3N4 and dry it. Repeat the above process 5 times to investigate the reusability of the visible light photocatalytic composite material. The results are shown in Table 1. Figure 6 .
[0048] Figure 1 The photocatalytic activity test results show that Examples 1 and Examples 5-7 all have good photocatalytic performance, among which the thiolated Fe3O4@TiO2 / g-C3N4 prepared in Example 1 has the strongest photocatalytic ability and the fastest reaction, with methyl orange being degraded by more than 90% within 60 min.
[0049] Figure 2The FT-IR analysis results show that the samples in Examples 1-4 all have a wavelength of 1200-1650 cm -1 The characteristic absorption peaks of CN and C=N appear at 3400 cm -1 The stretching vibration peak of the surface hydroxyl group (-OH) appeared at 700 cm -1 and 2500-2600 cm -1 The absorption peak of 3300-3500 cm in Example 2 indicates that the thiol modification is successful. -1 The double peaks at 1040-1180 cm -1 The symmetric and asymmetric stretching vibration peaks of the S=O bond are shown, 600-800 cm in Example 4. -1 Peak is COO - Bending vibration peaks of the group.
[0050] Figure 3 The XRD results correspond to the FT-IR analysis results. The surface modification groups do not change the crystal form of the composite material and still retain its efficient photocatalytic ability.
[0051] Figure 4 The UV-Vis DRS diffuse reflectance results showed that the photocatalytic spectra of group-modified Fe3O4@TiO2 / g-C3N4 prepared from different raw materials were different. The absorption band edge was in the range of 515-540 nm, and the visible light wavelength range that triggered photocatalysis was increased, and they all had high photocatalytic performance.
[0052] Figure 5 The group-modified Fe3O4@TiO2 / g-C3N4 prepared in Examples 1-4 has specific adsorption behavior for heavy metal ions, and thiolation is beneficial to the adsorption of Pb 2+ 、Cd 2+ 、Ag + , amination is beneficial to the adsorption of Cu 2+ Cr 3+ , sulfonic acid groups on Pb 2+ Cr 3+ 、Al 3+ The adsorption capacity is strong. EDTA has a broad-spectrum multi-dentate adsorption capacity due to its abundant amino and carboxyl groups.
[0053] Figure 6 The photocatalytic reuse performance test results of the methyl orange solution showed that the thiolated Fe3O4@TiO2 / g-C3N4 prepared in Example 1 has the characteristic of being reusable, and the photocatalytic degradation efficiency is still higher than 80% after being reused 5 times.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
[0055] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A visible light photocatalytic composite material, characterized in that: The visible light photocatalytic composite material comprises the following raw materials by weight: 10-50 g of magnetic nanocore, 20-80 g of TiO2 precursor, 20-80 g of stabilizer, 40-100 g of g-C3N4 precursor and 50-200 g of modifier, and the magnetic nanocore comprises the following raw materials by weight: 27-54 g of FeCl3·6H2O, 20-40 g of FeSO4·7H2O and 50-100 g of 25% NH4OH solution.
2. The visible light photocatalytic composite material according to claim 1, characterized in that: The modifying agent is selected from any one of MPTS, ethylenediamine, chlorosulfonic acid and EDTA-2Na.
3. The visible light photocatalytic composite material according to claim 1, characterized in that: The preparation process of the magnetic nanocore specifically comprises the following steps: S1: Weigh FeCl3·6H2O and dissolve it in deionized water to obtain FeCl3 solution; S2: Weigh FeSO4·7H2O and add it to FeCl3 solution, stirring and dissolving to obtain an iron salt solution; S3: After heating the iron salt solution, add 25% NH4OH solution to adjust the pH and react to obtain Fe3O4 precipitation; S4: Separate the Fe3O4 precipitate, wash it, and dry it to obtain the magnetic nanocore.
4. The visible light photocatalytic composite material according to claim 3, characterized in that: In step S1, the mass volume ratio of the FeCl3·6H2O and deionized water is 2.7-5.4 g:100 mL; In step S3, the heating and pH adjustment process is carried out under a nitrogen atmosphere, and the pH is adjusted to 10.0±0.
2.
5. The visible light photocatalytic composite material according to claim 4, characterized in that: The TiO2 precursor is selected from any one of Ti(OBu)4, Ti(OiPr)4 and LiTiO3; The stabilizer is selected from any one of acetic acid, acetylacetone, ethyl acetate and triethanolamine; The g-C3N4 precursor is selected from any one of urea, dicyandiamide, thiourea and citrulline.
6. A method for preparing a visible light photocatalytic composite material according to any one of claims 1 to 5, characterized in that: The specific steps include: Step 1: weigh the magnetic nanocores to prepare a dispersion; Step 2: Weigh the TiO2 precursor and stabilizer and add them to the dispersion to obtain a Fe3O4@TiO2 reaction solution; Step 3: Weigh the g-C3N4 precursor and add it to the Fe3O4@TiO2 reaction solution for reaction, collect the precipitate and calcine it to obtain Fe3O4@TiO2 / g-C3N4; Step 4: Hydroxylating Fe3O4@TiO2 / g-C3N4 to obtain hydroxylated Fe3O4@TiO2 / g-C3N4; Step 5: Use a modifier to modify the hydroxylated Fe3O4@TiO2 / g-C3N4 to obtain a visible light photocatalytic composite material.
7. The method for preparing a visible light photocatalytic composite material according to claim 6, characterized in that: In step 1, the dispersion is prepared by dispersing the magnetic nanocores in a 40% volume fraction ethanol aqueous solution; In step 3, the reaction process is carried out in a high-pressure reactor, the collection and precipitation process uses a magnetic separator, and the calcination process is carried out in a tubular furnace; In step 4, the hydroxylation process is as follows: Fe3O4@TiO2 / g-C3N4 is immersed in a H2SO4-H2O2 mixed solution, a precipitate appears, and the precipitate is filtered, washed with deionized water, and dried.
8. The method for preparing a visible light photocatalytic composite material according to claim 7, characterized in that: When the modifier is MPTS, step 5 specifically includes the following steps: dispersing hydroxylated Fe3O4@TiO2 / g-C3N4 in anhydrous ethanol, weighing MPTS and adding acetic acid to react, using acetic acid as a catalyst, obtaining a precipitate after the reaction is completed, transferring the precipitate and washing and drying it with anhydrous ethanol to obtain thiolated Fe3O4@TiO2 / g-C3N4, i.e., a visible light photocatalytic composite material.
9. The method for preparing a visible light photocatalytic composite material according to claim 7, characterized in that: When the modifier is EDTA-2Na, step 5 specifically includes the following steps: preparing an EDTA-2Na aqueous solution, dispersing the hydroxylated Fe3O4@TiO2 / g-C3N4 in deionized water, adding an equal volume of EDTA-2Na solution thereto, heating and reacting, transferring the precipitate and washing and drying it with anhydrous ethanol to obtain EDTA-treated Fe3O4@TiO2 / g-C3N4, i.e., a visible light photocatalytic composite material.
Citation Information
Patent Citations
Preparation method of composite photocatalytic material of Fe3O4-N doped with Ni / Zn-MOFs / g-C3N4
CN108579819A
Magnetic metal organic framework nano material with three layers of core-shell structures, preparation method and application thereof
CN109126721A
Metal-adsorbing composite material based on magnetic graphene oxide and method for obtaining same
WO2021148700A1
Cited By
Photoresponse biomass-based material for removing organic-inorganic combined pollution in water as well as preparation method and application of photoresponse biomass-based material
CN121202235A